Tradition old and new - Bruce, Frederick Fyvie, 1910-90; Southern Baptist Theological Seminary Louisville, KE.; Richmond College London, UK. (Exeter, UK Paternoster, 1978)
Includes bibliographical references and indexes.
Norton Lectures on Religion and Science, Southern Baptist Theological Seminary, Louisville, Kentucky, March, 1968. Parts of Chapters 8 and 9 from the Ryder Smith Memorial Lecture, Richmond College, London, October 17, 1968.
Keywords: Bible. N.T. -- criticism, interpretation, etc